2004
DOI: 10.1002/ajmg.a.30312
|View full text |Cite
|
Sign up to set email alerts
|

Ocular coloboma and high myopia with Hirschsprung disease associated with a novel ZFHX1B missense mutation and trisomy 21

Abstract: Syndromic Hirschsprung disease has been associated with mutations in ZFHX1B, a Smad-interacting transcriptional repressor protein. Tissue in situ hybridization has demonstrated strong expression of ZFHX1B in the developing eye, suggesting that some mutations in this gene may cause visual loss. However, none of the reported mutations have been associated with an ocular phenotype. We describe a patient with Down syndrome and Hirschsprung disease with high myopia and ocular coloboma affecting the iris and retina.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
43
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 30 publications
2
43
0
Order By: Relevance
“…A comparison with the literature data is provided in Table IV. Genotype-phenotype correlations should be carefully considered, since some patients with in-frame, missense, or splice site mutations were reported with an atypical clinical presentation [Yoneda et al, 2002;Gregory-Evans et al, 2004]. In all our cases, mutations were de novo mutations, occurring sporadically in families with one only exception, consisting of two affected sisters with the same nonsense, novel mutation not detected in the phenotypically normal parents [Cecconi et al, 2008].…”
Section: Genotypementioning
confidence: 80%
See 2 more Smart Citations
“…A comparison with the literature data is provided in Table IV. Genotype-phenotype correlations should be carefully considered, since some patients with in-frame, missense, or splice site mutations were reported with an atypical clinical presentation [Yoneda et al, 2002;Gregory-Evans et al, 2004]. In all our cases, mutations were de novo mutations, occurring sporadically in families with one only exception, consisting of two affected sisters with the same nonsense, novel mutation not detected in the phenotypically normal parents [Cecconi et al, 2008].…”
Section: Genotypementioning
confidence: 80%
“…This represents the fourth instance of sibling recurrence [McGaughran et al, 2005;Zweier et al, 2005;Mowat, personal communication;Ohtsuka et al, 2008], due to most likely germ-line mosaicism. Lurie et al [1994], Mowat et al [1998Mowat et al [ , 2003, Amiel et al [2001], Cacheux et al [2001], Kaariainen et al [2001], Rauch et al [2001], Wakamatsu et al [2001], Yamada et al [2001], Nagaya et al [2002], Yoneda et al [2002], Zweier et al [2002Zweier et al [ , 2003Zweier et al [ , 2005Zweier et al [ , 2006, Garavelli et al [2003], Sztriha et al [2003], Wilson et al [2003], Cerruti-Mainardi et al [2004], Gregory-Evans et al [2004], Horn et al [2004], Ishihara et al [2004], Silengo et al [2004], Garavelli et al [2005], McGaughran et al [2005], , Adam et al [2006Adam et al [ , 2008a, Heinritz et al [2006], , Dastot-Le et al [2007], Garavelli and Cerruti Mainardi [2007], Hoffer et al [2007], Sasongko et al [2007], Strenge et al [2007], , Ohtsuka et al [2008], Sasso et al [2008]. b Without the six cases already published [Garavelli et al, 2003;Cerruti-Mainardi et al, 2004;…”
Section: Genotypementioning
confidence: 99%
See 1 more Smart Citation
“…The siblings presented here have a typical range of other phenotypic abnormalities seen in the condition. However, this is only the second report of ocular coloboma in patients with proven ZFHX1B mutation [Gregory-Evans et al, 2004]. The patient reported by Gregory-Evans et al, who had trisomy 21, HSCR and a phenotype considered not consistent with MWS, had a missense mutation in ZFHX1B, whereas to date all published mutations in typical MWS have been truncating or null, including the mutation in these siblings.…”
Section: Discussionmentioning
confidence: 76%
“…Several studies link Sip1 to the development and function of the eye: ocular coloboma has been reported in a carrier of a missense mutation in SIP1, a genome-wide association study has implicated the involvement of SIP1 in high myopia in humans, and in the mouse Sip1 is required for normal lens development (Gregory-Evans et al, 2004;Khor et al, 2013;Manthey et al, 2014;Yoshimoto et al, 2005). Considering these important roles of Sip1 in neurogenesis and eye development we aimed in this study to uncover its contributions to retinogenesis.…”
Section: Introductionmentioning
confidence: 99%